Facile and efficient synthesis of C2-symmetrical 1,3,5-triazine polycarboxylate ligands under microwave irradiation - Watcharee Funfuenha (2018)
© 2014 Elsevier Ltd. All rights reserved. A rapid and efficient method for preparation of C 2 -symmetrical 1,3,5-triazine polycarboxylate ligands was developed. The reactions included either selective mono- or di-substitution of 2,4,6-trichloro-1,3,5-triazine with various nucleophiles containing carboxyl group(s), followed by nucleophilic displacement of the remained chloride(s) in aqueous media under microwave irradiation. Novel C 2 -symmetrical tripodal ligands were afforded in good yields and purities under short reaction time with simple work-up, which are potentially useful as structural directing units in metal-organic frameworks.